The involvement of physico-chemical interactions in the adhesion of Candida albicans and Candida dubliniensis to epithelial cells - Henriques, Mariana (2007)
Candida albicans and Candida dubliniensis are two pathogenic yeasts particularly hazardous to immunocompromised patients. Adhesion of yeast cells to epithelium is considered one of the virulence factors and its study is of major importance. The main aim of this study was the comparison of the influence of physico-chemical properties on the adhesion of C. albicans and C. dubliniensis to epithelium. Two strains of each Candida species were used in the adhesion assays to HeLa cells. Adhered cells were enumerated by direct microscopic images observation. Yeast cell surface tension parameters and degree of hydrophobicity were determined by contact angle measurement. Pseudohyphae and hyphae formation was analysed by scanning electron microscopy. Yeast cells presented no statistical differences concerning their physico-chemical surface properties. However, the extent of adhesion to epithelium was different among the four strains. As general conclusion, yeast adhesion to epithelium seems to be strain-dependent and not directly correlated with pseudohyphae formation.